Efektivitas Terapi Relaksasi Autogenik terhadap Kecemasan Pre Operasi Bedah Abdomen di RS Permata Medika Semarang - Janiar Puspita Sari; Endang Supriyanti; Dyah Restuning P (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Surgery is an invasive medical procedure performed to diagnose or treat physical abnormalities, diseases, or injuries. However, surgery often causes anxiety in patients, especially in the preoperative phase. This study aims to determine the effect of autogenic relaxation therapy on the anxiety levels of preoperative abdominal surgery patients at Permata Medika Hospital, Semarang. This study used a one-group pretest-posttest design without a control group. The study population was preoperative abdominal surgery patients experiencing anxiety. The sampling technique used purposive sampling with a total of 50 respondents. Anxiety levels were measured before the intervention (pretest) and after the intervention (posttest). The autogenic relaxation therapy intervention was given for 15 minutes to each respondent. This therapy was carried out by providing calming suggestions and training in focusing attention on body sensations to help reduce physical and psychological tension. The results showed a decrease in patient anxiety levels after autogenic relaxation therapy compared to before the intervention. Thus, autogenic relaxation therapy can be used as a non-pharmacological nursing intervention to help reduce anxiety in preoperative abdominal surgery patients.